Avaliação pós-ocupação da habitação de interesse social no Brasil: uma revisão sistemática da literatura - SANTOS, Laira Vasconcelos dos (Universidade Federal do Pará, 2017)
This study corresponds to the systematic review of the literature (SRL) on Post Occupancy Evaluation (POE) of Social Housing in Brazil (SHB), produced in the 2013-2014 period. CAPES, Scielo, Habitare Collection, Repository of universities and academic google were the databases used for research. Thirty-eight studies were carefully selected for analysis, based on criteria of inclusion and exclusion. We conducted an analysis of studies from the classification of the nature of the assessment of impacts and results for evidence. The studies were conducted mainly in the South and Southeast, it was not located any studies in the North, and the ratings are most frequent in recent years (2011-2014). The evidence was analyzed according to the nature of the assessment (outcome or impact) and the main evidence cited in the results of evaluation studies were dissatisfaction with housing typology, lack of constructive flexibility, recurrent constructive modifications (reforms / changes) of functional character, symbolic or economic, insufficient size of the housing unit, excessive standardization of housing units, location (cheap land, large areas devoid of infrastructure), low cost and quality material, predominantly-condo increased expenses, noncompliance / failure of normative of housing programs. And in impact assessments found the exclusion of the right to the city, uniformity, mass assemblies, the standardization of housing solutions, mono-functional sets, the lack of security, lack of urban integration by the lack of infrastructure and poor location, (In ) families remain in housing units, except adaptation (physical and budget), that residents do not participate in project planning, the feedback data of assessments does not occur and the irregular transfer of housing units. We conclude that the POE is an appropriate tool for evaluating the housing policy.